Seasonal and Annual Fluxes of Nutrients and Organic Matter from Large Rivers to the Arctic Ocean and Surrounding Seas - Holmes, Robert Max; McClelland, James W.; Peterson, Bruce J.; Tank, Suzanne E.; Bulygina, Ekaterina; Eglinton, Timothy I.; Gordeev, Viacheslav V.; Gurtovaya, Tatiana Y.; Raymond, Peter A.; Repeta, Daniel J.; Staples, Robin; Striegl, Robert G.; et al. (Estuaries and coasts, 2012)
River inputs of nutrients and organic matter impact the biogeochemistry of arctic estuaries and the Arctic Ocean as a whole, yet there is considerable uncertainty about the magnitude of fluvial fluxes at the pan-Arctic scale. Samples from the six largest arctic rivers, with a combined watershed area of 11.3 x 10⁶ km², have revealed strong seasonal variations in constituent concentrations and fluxes within rivers as well as large differences among the rivers. Specifically, we investigate fluxes of dissolved organic carbon, dissolved organic nitrogen, total dissolved phosphorus, dissolved inorganic nitrogen, nitrate, and silica. This is the first time that seasonal and annual constituent fluxes have been determined using consistent sampling and analytical methods at the pan-Arctic scale and consequently provide the best available estimates for constituent flux from land to the Arctic Ocean and surrounding seas. Given the large inputs of river water to the relatively small Arctic Ocean and the dramatic impacts that climate change is having in the Arctic, it is particularly urgent that we establish the contemporary river fluxes so that we will be able to detect future changes and evaluate the impact of the changes on the biogeochemistry of the receiving coastal and ocean systems.